Deciphering the evolving niche interactome of human hematopoietic stem cells from ontogeny to aging - Feng, Cong; Fan, Haoyan; Tie, Ruxiu; Xin, Saige; Chen, Ming (Frontiers in Molecular Biosciences, 2024)
Hematopoietic stem cells (HSC) reside within specialized microenvironments that undergo dynamic changes throughout development and aging to support HSC function. However, the evolving cell-cell communication networks within these niches remain largely unexplored. This study integrates single-cell RNA sequencing datasets to systematically characterize the HSC niche interactome from ontogeny to aging. We reconstructed single-cell atlases of HSC niches at different developmental stages, revealing stage-specific cellular compositions and interactions targeting HSC. During HSC maturation, our analysis identified distinct patterns of ligand-receptor interactions and signaling pathways that govern HSC emergence, expansion, and maintenance. HSC aging was accompanied by a decrease in supportive niche interactions, followed by an adaptive increase in interaction strength in old adult bone marrow. This complex aging process involved the emergence of interactions associated with inflammation, altered stem cell function, and a decline in the efficacy of key signaling pathways. Our findings provide a comprehensive understanding of the dynamic remodeling of the HSC niche interactome throughout life, paving the way for targeted interventions to maintain HSC function and promote healthy aging. This study offers valuable insights into the intricate cell-cell communication networks that govern HSC behavior and fate, with implications for hematological disorders and regenerative medicine.